Navigating Through the Caregiving Trajectory: A Qualitative Interview Study on the Challenges Encountered by Primary Caregivers When Caring for Adolescents Living with HIV - Jeaneth Linki Matsimbi; Maditobane Robert Lekganyane (Nursing Reports, 2026)
Background/Objectives: Children and adolescents living with HIV (ALHIV) are among the most vulnerable groups affected by HIV and AIDS. Their vulnerability exposes them to several challenges, such as HIV-related stigma and/or interrupted academic activities due to health-related complications. Since they are still minors who cannot independently make decisions regarding their own lives, most of the challenges extend to their caregivers, who sometimes provide care and support under difficult psychological, social, and economic conditions. This study aimed to explore the lived experiences and challenges of primary caregivers caring for ALHIV in Gauteng Province of South Africa. Methods: A qualitative exploratory design with phenomenological orientation was adopted. Eight primary caregivers of ALHIV were purposively sampled and interviewed using individual face-to-face semi-structured interviews. Data was analysed thematically according to the eight steps of Tesch’s qualitative analysis framework. Since it involved human participants, this study was subjected to ethical clearance by the Research Ethics Committee of the University of South Africa, which imposed conditions for upholding ethical principles such as informed consent and confidentiality. Results: Primary caregivers encounter challenges such as regular monitoring of ALHIV who are always sick, treatment adherence monitoring, behavioural management, financial strain, stigma and discrimination, lack of proper nutrition and managing adolescents’ academic difficulties. These challenges require support from multidisciplinary team members which include nurses because they play a crucial role in supporting treatment adherence among ALHIV and in strengthening the capacity of primary caregivers to provide effective treatment support. Conclusions: It is essential to adopt an integrated approach to psychosocial, as well as financial support interventions targeting primary caregivers.